2021
DOI: 10.1002/chem.202103672
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐Catalyzed RNA‐Oligomerization from 3’,5’‐cGMP

Abstract: The assembly of ancient informational polymers from nucleotide precursors is the central challenge of life's origin on our planet. Among the possible solutions, dry polymerization of 3’,5’‐cyclic guanosine monophosphate (3’,5’‐cGMP) has been proposed as a candidate to create oligonucleotides of 15–20 units in length. However, the reported sensitivity of the reaction to the presence of cations raised questions of whether this chemistry could be relevant in a geological context. The experiments in this study sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…8,9 We base this study on 2´,3´-cyclic mononucleotides (cNMP) which (a) possess an intrinsically activated phosphate; (b) are products of several prebiotic phosphorylation and nucleotide syntheses; [10][11][12][13][14] and (c) are products of neutral to alkaline chemical and enzymatic hydrolyses of RNA. [15][16][17][18][19] In comparison, the dry polymerisation of 3´,5´-cyclic GMP, [20][21][22] did not foster the copolymerisation of the other nucleotides. 22 We found that 2´,3´-cGMP polymerised spontaneously under alkaline (pH [7][8][9][10][11][12], drying conditions (40-80 °C).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…8,9 We base this study on 2´,3´-cyclic mononucleotides (cNMP) which (a) possess an intrinsically activated phosphate; (b) are products of several prebiotic phosphorylation and nucleotide syntheses; [10][11][12][13][14] and (c) are products of neutral to alkaline chemical and enzymatic hydrolyses of RNA. [15][16][17][18][19] In comparison, the dry polymerisation of 3´,5´-cyclic GMP, [20][21][22] did not foster the copolymerisation of the other nucleotides. 22 We found that 2´,3´-cGMP polymerised spontaneously under alkaline (pH [7][8][9][10][11][12], drying conditions (40-80 °C).…”
Section: Introductionmentioning
confidence: 95%
“…[15][16][17][18][19] In comparison, the dry polymerisation of 3´,5´-cyclic GMP, [20][21][22] did not foster the copolymerisation of the other nucleotides. 22 We found that 2´,3´-cGMP polymerised spontaneously under alkaline (pH [7][8][9][10][11][12], drying conditions (40-80 °C). The other canonical cNMP were relatively inert under similar conditions.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We base this study on 2´,3´-cyclic mononucleotides (cNMP) which (a) possess an intrinsically activated phosphate; (b) are products of several prebiotic phosphorylation and nucleotide syntheses; [14][15][16][17][18] and (c) are products of neutral to alkaline chemical and enzymatic hydrolyses of RNA. [19][20][21][22][23] In comparison, the dry polymerisation of 3´,5´-cGMP [24][25][26] did not foster the polymerisation of the other ribonucleotides. [26] Orgel and coworkers, reported conditions for 2´,3´-cAMP polymerisation by drying for 40 days with a 5-fold excess of ethane-1,2-diamine and yields up to 0.67% of 14-mers.…”
Section: Introductionmentioning
confidence: 95%
“…[19][20][21][22][23] In comparison, the dry polymerisation of 3´,5´-cGMP [24][25][26] did not foster the polymerisation of the other ribonucleotides. [26] Orgel and coworkers, reported conditions for 2´,3´-cAMP polymerisation by drying for 40 days with a 5-fold excess of ethane-1,2-diamine and yields up to 0.67% of 14-mers. [4,6] Other catalysts such as imidazole or urea required temperatures up to 85°C and offered lower yields.…”
Section: Introductionmentioning
confidence: 95%